Adsorption of low-concentration mercury in water by 3D cyclodextrin/graphene composites: Synergistic effect and enhancement mechanism. (September 2019) - Qiu, Peipeng; Wang, Shuting; Tian, Chen; Lin, Zhang
Abstract: The efficient removal of mercury from aqueous media remains a severe challenge in ensuring environmental safety, especially for low-concentration mercury, which requires adsorbents with high mercury affinity. In this work, we reported a nanocomposite of β-cyclodextrin and three-dimensional graphene (3D CD@RGO) to enhance the adsorption affinity and capacity for mercury with low concentrations. Characterization of the nanocomposite revealed that cyclodextrin was well dispersed on the 3D graphene support structure to provide highly exposed hydroxyl groups. Adsorption experiments showed that CD@RGO exhibited different adsorption behaviors for mercury within different concentration ranges of 0.2–4.0 mg/L and 4.0–10.0 mg/L, and the adsorption affinity for the former range ( K L = 10.05 L/mg) was 1.5 times higher than that for the latter range ( K L = 6.69 L/mg). Moreover, CD@RGO had a high adsorption efficiency of 96.6% with a superb adsorption affinity (172.09 L/g) at C e = 0.01 mg/L, which is 6.70 and 41.25 times higher than that of RGO and RCD (physical mixture of RGO and cyclodextrin), respectively, indicating a synergistic effect of CD@RGO for mercury adsorption. This enhancement can be attributed to the transformation of the adsorption mechanism from the outer-sphere force of electrostatic interaction in RGO to the inner-sphere surface complexation in CD@RGO. Graphical abstract: Image 1 Highlights: 3D composites had different adsorption behaviors for different mercury concentrations. 3D composites showed outstanding adsorption affinity for low concentration mercury. Hydroxyl-mercury inner-sphere complexation was the capture mechanism. Abstract : This work provides a novel idea to increase the adsorption affinity for mercury, which will promote the advanced methods for removing low-concentration mercury.